二次型f(x1,x2,x3)=(x1+x2)2+(x2-x3)2+(x3+x1)2的秩为()。
A: 1
B: 2
C: 3
D: 4
A: 1
B: 2
C: 3
D: 4
举一反三
- 青书学堂: 二次型 f( x 1 , x 2 , x 3 )=2 x 1 2 +5 x 2 2 +5 x 3 2 +4 x 1 x 2 −8 x 2 x 3 ,则 f的矩阵为 。
- 二次型f(x1,x2,x3)=(x1+x2)2+(x2-x3)2+(x3+x1)2的秩为()。 A: 1 B: 2 C: 3 D: 4
- 求函数 f(x)=3*x1^2 + 2*x1*x2 + x2^2 − 4*x1 + 5*x2. 时,输入代码 >>fun = @(x)3*x(1)^2 + 2*x(1)*x(2) + x(2)^2 - 4*x(1) + 5*x(2); >>x0 = [1,1]; >>[x,fval] = fminunc(fun,x0); 其中fun的作用是:
- 求方程组的解,取初值为(1,1,1)。[img=250x164]180333307ab8fde.jpg[/img] A: f=@(x) [x(1)^3+x(2)-x(3)-5; 2*x(1)+3*x(2)^2-6; x(1)+x(2)+x(3)-3];x=fsolve(f,[1,1,1],optimset('Display','off')) B: x=fsolve(@(x) [x(1)^3+x(2)-x(3)-5; 2*x(1)+3*x(2)^2-6; x(1)+x(2)+x(3)-3],[1,1,1]) C: f=@(x) [x(1)^3+x(2)-x(3)-5; 2*x(1)+3*x(2)^2-6; x(1)+x(2)+x(3)-3];x=fzero(f,[1,1,1]) D: x=fzero(@(x) [x(1)^3+x(2)-x(3)-5; 2*x(1)+3*x(2)^2-6; x(1)+x(2)+x(3)-3],[1,1,1])
- 二次型f(x1,x2,x3)=(x1+x2)2+(x2-x3)2+(x3+x1)2的秩为()。 A: 0 B: 1 C: 2 D: 3